Follies and sanities in Don Quixote’s justice - Trujillo Silva, Joaquín (2021)
There is a tension between good senses and folly in the very act of justice, a tension that Don Quixote embodies. In his moments of insanity, Don Quixote is a vigilante; in his moments of sanity, a jurist. These two Quixotes appear and reappear throughout the novel, but they take on special significance in the testimony of outraged ladies, as well as at the end when the knight recovers his sanity and resolves his patrimonial problems before testament. Finally, the article proposes that for Cervantes folly is a condition of possibility of justice in the world.